Dampak Klorofluorokarbon Terhadap Lingkungan Hidup - Sumingkrat Sumingkrat (Jurnal Kimia dan Kemasan, 1998)
As the first step in tackling environmental issues related to the protection of the ozone layer have been reviewed internationally. In Indonesia under the "Law concerning the Protection of the Ozone Layer by Means of Regulation on Specified Substance", regulations on the production and importation of controlled CFCs have been enforced since March 1991. The problems with CFCs are primarily environmental. CFCs destroy the stratospheric ozone layer that protects people from harmful ultraviolet rays from the sun. Already, holes and breaks in the ozone layer are apparent to scientists. Without the ozone layer's protective shild, skin cancer and eye damage are more likely among people,and the marine food chain could be profoundly disrupted. In addition, CFCs are responsible for about one-fifth of the greenhouse gases emitted into the atmosphere every year.